Beach morphology and shoreline evolution: monitoring and modelling medium-term responses (Portuguese NW coast study site) - Baptista, P.
Numerical models for shoreline evolution have been used for coastal management planning for several decades. The model calibration is a start point to project shoreline scenarios and in this aimthe use of data acquiredwithin the scope of monitoring programmes provides the opportunity to assess the models' capabilities under real condition. This work applies calibration data (retrieved from field surveys) to numerical models to predict medium-term shoreline evolution using, as a case study, a beach stretch named AC, about 3.5 km long and located downdrift of a groin on the northwest Portuguese coast. A smaller stretch AB (2.4 km long), included in the total one, which exhibits a pronounced erosive tendency usually better reproduced in shoreline evolution models,was also analysed. Based on topographic surveys, associatedwave climate conditions registered between 2003 and 2008 and typical wave conditions registered over a longer wave climate time period, this work compares the calibration of two different shoreline evolution models, Long-term Configuration (LTC) and GENESIS for this period. Then, considering the 2003 topographic conditions for themodels' calibration, the results of both models are discussed with respect to simulation scenarios after 10, 15 and 20 years of evolution. The 10-year evolution projections of the models are also compared to the results of a survey performed in February 2012. For the wave data calibration period (2003–2008), the average shoreline retreat of the analysed coastal stretch was reproduced with small differences (around 1% and 10% for LTC and 15% and 14% for GENESIS, considering stretches AB or AC, respectively), though local differences along the AB coastal stretch represent root mean square errors reaching up to 52% and 88% for GENESIS and LTC, respectively, and were above 118% for both models along the AC coastal stretch.